Systemic Lupus Erythematosus Associated with Neurological Manifestations in a Border Collie Bitch - Rodrigues Rosado, Isabel; Perinotto Picelli, Julia; Gonzaga da Silva, Juliana; Cazarini Madeira, Marina; Teixeira Zambarda, Taís; Gabellini Leonel Alves, Endrigo (Acta Scientiae Veterinariae, 2021)
Background: Systemic lupus erythematosus (SLE) is an immune-mediated and multisystemic disorder which etiology is believed to be multifactorial. Its clinical signs vary accordingly to affected organs, cutaneous lesions being the most frequently observed. There are few reports of SLE in dogs with neurological manifestations. Therefore, the aim of this report is to describe a case of SLE in a dog with indicative signs of nervous system involvement. Case: A 6-year-old Border Collie bitch was referred to the Veterinary Hospital (HVU) of the University of Uberaba (UNIUBE) with a history of with cluster seizures, inappetence and urinary incontinence. Erythema and flaking of nasal plan were noted on physical examination, and splenomegaly on abdominal palpation. Thrombocytopenia and slightly increased ALT were found on blood tests. Ehrlichiosis was suspected and doxycycline was prescribed together with phenobarbital for the control of seizures. In the follow-up visit, the dog was still presenting urinary incontinence, thrombocytopenia and splenomegaly. Also, an ulcer on the nasal mucocutaneous junction was observed. The patient went through a neurological examination which indicated thalamocortical lesion. Cerebrospinal fluid samples were obtained for cytology, culture and canine distemper test, and serology tests for leishmaniasis, toxoplasmosis and neosporosis were done. No alterations were found in these exams. The histopathology of the nasal lesion was proceeded and showed results consistent with lupus erythematosus. It was prescribed a 15-day course of prednisolone at immunosuppressive dose. The patient showed clinical improvement with this treatment. Azathioprine was started along with gradual removal of prednisolone. After twenty days of discontinuation of this drug, the dog presented epileptic seizures, urinary incontinence, thrombocytopenia, increased ALT and worsened nasal lesion. Prednisolone at immunosuppressive dose was reintroduced and the dose of azathioprine, increased. One week past this, the patient showed inappetence and an extensive hematoma in the thoracic region. Lab exams confirmed drug-induced acute pancreatitis. All medications were interrupted, the patient was hospitalized, and treatment for pancreatitis was initiated, but the dog passed away. Discussion: For involving multiple body systems and for presenting varied clinical signs, diagnosing SLE can be challenging in clinical routine. The dog from this report was a Border Collie; this breed is considered to be predisposed to this disease. The animal had a history of being exposed to solar radiation for a large part of the day, had dyspigmentation of nasal plan and had no application of sunscreen, predisposing the occurrence of SLE. Neurological signs are uncommon in SLE, but the seizures and the urinary incontinence were the main reasons for the dog’s guardian to look for medical assistance. The suspicion for SLE was raised due to cutaneous manifestations and persistent thrombocytopenia along with splenomegaly. Histopathological findings are essential for diagnosing SLE, as well as antinuclear antibody tests. Nonetheless, due to financial limitations, this last test was not performed. Azathioprine is an immunomodulating drug largely used along with glucocorticoids when treating SLE; however, this medication is prone to induce side effects as the ones presented by the dog from this report. Therefore, it is concluded that SLE should be considered as a differential diagnosis in patients showing cutaneous, hematological, systemic and neurological manifestations, considering the variety of signs caused by this disorder. Keywords: seizures, dog, immune-mediated encephalopathy. Lúpus eritematoso sistêmico associado a manifestações neurológicas em cadela da raça Border Collie Descritores: crises epilépticas, cão, encefalopatia imunomediada.